Synthesis and Characterization of Nanosized Zinc Stanate for Thermal Application (Indian Journal of Chemistry (IJC), 2025)
Nano sized bimetallic oxide materials have been extensively studied worldwide because of their unique properties and applications. The facial approach to preparing well dispersed nanocrystals of zinc stanate (ZnSnO3) using Zn and Sn oxalate as precursors. Self-propagating high temperature synthesis method was adopted using polymer fuel. Combustion processed ZnSnO3 nanomaterials were confirmed by various characterization tools. X-Ray diffraction (XRD) tool is used to study the structure of the prepared bimetallic oxide nanomaterials sample. Morphological study of prepared sample was carried by scanning electron microscope (SEM) analysis. Bonding nature of the sample was studied by Fourier transfer infrared (FT-IR) tool and presence of the Zn and Sn are confirmation in the prepared sample was identified by EDX analysis respectively. Absorption study of the prepared sample was characterized by UV-Vis spectroscopy. Thermal behavior of the bimetallic oxide sample was analyzed by thermo gravimetric analysis (TGA), Raman spectroscopic (RS) study was undertaken to view its structural organization. Dynamic light scattering (DLS) study was implemented to know the size of the sample. Cyclic voltammetry (CV) study was also experimented to know the electrolytic behavior of the zinc stannate sample.